Análisis de los parámetros de diseño para un edificio con y sin aisladores en la base. (2019)
One of the great problems that arises in the Construction is the seismic response of a structure in the presence of an earthquake, usually for the design the seismic norms that ensure the safety of people are taken into account; however, the state in which the structure remains once the earthquake occurs is not taken into account. In this work an analysis was made of the parameters necessary for the design of a building with and without insulators, showing the advantages and disadvantages of the presence of these devices that will improve the seismic response of a building.